Unveiling the polar properties on barium bismuthate perovskite thin films with distinct Ba/Bi ratios - Acero, G. [UNESP]; Moreno, H. [UNESP]; Ortega, P. P. [UNESP]; Ramirez, M. A. [UNESP]; Ponce, M. A.; Moura, F.; Simões, A. Z. [UNESP] (Elsevier, 2024)
This research aims to investigate the domain structure of BaBiO3 (80:20), BaBiO3 (50:50), and BaBiO3 (30:70) thin films obtained by the polymeric precursor method. For better sample designations, the following codes were employed: (80:20) (BBO82), (50:50) (BBO55), and (30:70) (BBO37). The piezo-ferroelectric coupled behavior observed for barium bismuthates thin films was elucidated in terms of bismuth and oxygen vacancies as well as grain morphology, which can be controlled by stoichiometric changes (Ba/Bi ratios). The films crystallize in a rhombohedral BaBiO3 structure with an R-3R space group without any deleterious secondary phase. Additionally, the hysteretic strain, dielectric, ferroelectric, and piezoelectric properties of BaBiO3 thin films are strongly dependent on the film texture. Sample BBO55 showed a distinguished preferred orientation along the (341) plane with a low associated coercive field (66.87 kV/cm), free of imprint and with no polarizations gap compared to samples BBO37 and BBO82. Sample BBO55 presented the highest piezoelectric (d33-eff ≈ 45.7 pm/V) and ferroelectric (Pr≈19.87 μC/cm2) responses. This behavior can be ascribed to a highly textured film, which generates less strain throughout the crystal lattice, facilitating the polarization switching mechanism and improving piezo/ferroelectricity. These findings are significant for developing novel, high-performance, lead-free piezoelectric materials to be applied in different electronic components such as magnetic field sensors, switches, actuators, and other types of memory devices.
Keywords: BaBiO3; Ferroelectric; Piezoelectric; Polymeric Precursor Method; Thin film